Hubungan Waktu Tanggap Kegawatdaruratan dengan Tingkat Kepuasan Pasien di Instalasi Gawat Darurat RSUD Kabupaten Bekasi - Zeni Wulandari; Sahrudi Sahrudi (Malahayati Nursing Journal, 2024)
ABSTRACT The development of health services reflects efforts to adapt to the global world, marked by intense competition between public and commercial hospitals. Customers have access to sufficient information and can choose from a variety of alternative services in a highly competitive environment. Basuki (2015) stated that in order for hospitals to be able to outperform their competitors to get new clients, they must be able to offer superior health services so as to satisfy patients and families. Emergency response time on the level of patient satisfaction in the Emergency Room of the Bekasi District Hospital in 2023. The research design used in this research is correlational by using the cross sectional study method or research conducted where the collection of all variables is carried out at one and the same time.From the results of bivariate analysis, a p value = 0.004 (p0.05) was obtained, so that it can be said that there is a significant relationship between response time and patient satisfaction at the Emergency Room at Bekasi Regency Hospital in 2023. From the results of the bivariate analysis, it was obtained a p value = 0.004 (p 0.05), it can be concluded that there is a significant relationship between response time and the level of patient satisfaction at the Emergency Room at the Bekasi Regency Hospital in 2023. Keywords: Emergencies, Satisfaction Level  ABSTRAK Perkembangan layanan kesehatan mencerminkan usaha untuk beradaptasi dengan dunia global, ditandai dengan persaingan ketat antara rumah sakit publik maupun komersial. Pelanggan memiliki akses ke informasi yang cukup dan dapa memilih dari berbagai layanan alternatif di lingkungan persaingan yang ketat. Basuki (2015) menyatakan bahwa agar rumah sakit mampu mengungguli pesaing mereka untuk mendapatkan klien baru, harus mampu menawarkan layanan kesehatan unggul sehingga memuaskan pasien serta keluarga. Waktu tanggap kegawatdaruratan terhadap tingkat kepuasan pasien di IGD RSUD Kabupaten Bekasi Tahun 2023. Desain penelitian yang digunakan dalam penelitian ini adalah korelasional dengan menggunakan metode penelitian cross sectional study atau penelitian yang dilakukan dimana pengambilan dari semua variabel dilakukan pada satu waktu yang bersamaan. Dari hasil analisa bivariat diperoleh nilai p value = 0,004 (p0,05), sehingga dikatakan terdapat hubungan yang signifikan pada waktu tanggap dan tingkat kepuasan pasien di Instalasi Gawat Darurat RSUD Kabupaten Bekasi pada tahun 2023. Dari hasil analisa bivariat diperoleh nilai p value = 0,004 (p0,05), dapat disimpulkan bahwa ada hubungan yang signifikan antara waktu tanggap dengan tingkat kepuasan pasien di Instalasi Gawat Darurat RSUD Kabupaten Bekasi pada tahun 2023. Kata Kunci: Kegawatdaruratan, Tingkat Kepuasan